Metabolic benefits of inhibition of p38α in white adipose tissue in obesity - Zhang, Shengjie (PLoS Biol, 2018)
p38 has long been known as a central mediator of protein kinase A (PKA) signaling in brown adipocytes, which positively regulate the transcription of uncoupling protein 1 (UCP-1). However, the physiological role of p38 in adipose tissues, especially the white adipose tissue (WAT), is largely unknown. Here, we show that mice lacking p38α in adipose tissues display a lean phenotype, improved metabolism, and resistance to diet-induced obesity. Surprisingly, ablation of p38α causes minimal effects on brown adipose tissue (BAT) in adult mice, as evident from undetectable changes in UCP-1 expression, mitochondrial function, body temperature (BT), and energy expenditure. In contrast, genetic ablation of p38α in adipose tissues not only markedly facilitates the browning in WAT upon cold stress but also prevents diet-induced obesity. Consistently, pharmaceutical inhibition of p38α remarkably enhances the browning of WAT and has metabolic benefits. Furthermore, our data suggest that p38α deficiency promotes white-to-beige adipocyte reprogramming in a cell-autonomous manner. Mechanistically, inhibition of p38α stimulates the UCP-1 transcription through PKA and its downstream cAMP-response element binding protein (CREB), which form a positive feedback loop that functions to reinforce the white-to-beige phenotypic switch during cold exposure. Together, our study reveals that inhibition of p38α is able to promote WAT browning and confer metabolic benefits. Our study also indicates that p38α in WAT represents an exciting pharmacological target to combat obesity and metabolic diseases.